PERAN UNITED NATIONS OFFICE ON DRUGS AND CRIME (UNODC) DALAM MEMERANGI KEJAHATAN NARKOBA DI AFGHANISTAN PERIODE 2017-2020 - Ayu Fitria Ningsih; M. Saeri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
This research analyzed how the influence of United Nations Office on Drugs and Crime (UNODC) as the international organization on Afghanistan illicit drug problem that occurred during the 2017-2020 period. Afghanistan suffer loss from illicit drug that exists in this country as increase of death rate, drugs addict, etc. The Afghan government has made efforts to reduce the number of drug distributions in their country, but these efforts are still not enough. Therefore, government began cooperation with UNODC that can increase the effectiveness of its performance in fighting drug crime in Afghanistan. This study used a qualitative method, with data collection techniques through literature study sourced from several books, journals, articles, and websites. This study uses the perspective of Pluralism and the theory of the Role of International Organizations. The focus theory of this discussion is UNODC roled as an actor described in Clive Archer's theory. The study shared that UNODC as an actor has important role in fighting against drug crime in Afghanistan with contributed through Afghanistan cooperation with its programs such as; regional programmes, country programmes and monitoring programmes. The program included new alternative planning, campaign to raise public awareness, and other activities. Keywords: Transnational crime, Illicit drugs, International Organizations.